2022
DOI: 10.1038/s41420-022-01171-6
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 enhances migration and invasion of trophoblasts by upregulating ARHGDIB via transcription factor PU.1

Abstract: As the main constituent cells of the human placenta, trophoblasts proliferate, differentiate, and invade the uterine endometrium via a series of processes, which are regulated exquisitely through intercellular signaling mediated by hormones, cytokines, and growth factors. Programmed cell death ligand 1 (PD-L1) is a biomarker of the response to immune checkpoint inhibitors and can regulate maternal-fetal immune tolerance during pregnancy progression. Recently, it was found that PD-L1 may regulate obstetric comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…HTR-8/SVneo is a cell line commonly used to explore trophoblast function ( Zhang R et al, 2022 ; Zhang D et al , 2023 ), and in this study we found that HTR-8/SVneo expressed NCK1 via Western blotting. Thus, to further explore the possible mechanism of NCK1 in uRM, we selected the trophoblast cell line HTR-8/SVneo.…”
Section: Discussionmentioning
confidence: 55%
“…HTR-8/SVneo is a cell line commonly used to explore trophoblast function ( Zhang R et al, 2022 ; Zhang D et al , 2023 ), and in this study we found that HTR-8/SVneo expressed NCK1 via Western blotting. Thus, to further explore the possible mechanism of NCK1 in uRM, we selected the trophoblast cell line HTR-8/SVneo.…”
Section: Discussionmentioning
confidence: 55%
“…extravillous trophoblasts EVTs) show high expression of PD-L1 but with no difference between healthy and GDM samples. High expression of PD-L1 on EVTs has been previously reported 26 . Contrastly, there was a significant decrease in expression of PD-L1 on CD45+ DB leukocytes from individuals with GDM (Figure 3b).…”
Section: Resultsmentioning
confidence: 79%
“…PD-1 and its ligand PD-L1 are expressed in syncytiotrophoblast, cytotrophoblasts and EVT (79). Here, they promote an immunosuppressive environment at the maternal-fetal interface (7981).…”
Section: Resultsmentioning
confidence: 99%
“…PD-1 and its ligand PD-L1 are expressed in syncytiotrophoblast, cytotrophoblasts and EVT (79). Here, they promote an immunosuppressive environment at the maternal-fetal interface (7981). Among their role in modulating maternal immune cells, PD-1 and PD-L1 expression by trophoblast cells results in macrophage polarization to an M2 phenotype, the dominant macrophage population in the decidua, resulting in increased CD14 macrophages (82).…”
Section: Resultsmentioning
confidence: 99%